Political economy of India's foreign policy - Chakrabarti, Radharaman (Calcutta, 1982)
Perhaps the first of its kind, the present work explores the inter action between domestic and international economic compul sions on the one hand, and the broad thrust of the foreign policy of a newly liberated and deve loping nation such as India, on the other. It has grown from the con viction, currently shared by ex perts in the field, that the tools of economic and political research should reinforce each other for a proper understanding of the premises of foreign policy making. Since among the developing countries India provides by far the most instructive instance of conscious policy making, with the long term objective of reducing economic dependency, and gra dually moving towards substan tive equality with other nations in the management of its foreign relations, the work concentrates on the measures adopted by the Indian government to achieve these ends. The period covered in the work, 1947-1977, is ex pected to provide a good glimpse of the progress and problems of a foreign policy, intended to remain independent of external manipulation. The work was done in the Department of Political Science. University of Washington, from September 1978 to to June 1979, when the author visited the USA as a post-doctoral fellow under the Indo-US Exchange gramme. Pro Professor George consultant of the Modelski, project, ac claimed the work as an attrac tive exposition of problems of Indian foreign economic policy.
Keywords: Economics